Politeness strategies in public apologies: the Malaysian context / Muhammad Aizat Azhari - Azhari, Muhammad Aizat (2015)
The importance of politeness and the limited Malaysian studies on politeness in apologies prompted this research to examine the use of politeness in Malaysian public apology texts. This study examined 50 Malaysian online naturally-occurring public apology texts from 2000 to 2012 for politeness in terms of apology strategies, positive politeness strategies and negative politeness strategies. The content analyses of apology strategies and politeness strategies were based on researchers’ apology taxonomies and Brown and Levinson’s (1987) Positive and Negative Politeness Strategies respectively. The content analyses provided four (4) important findings. First, the 50 individual Malaysian public apology texts reflected the use of a range of three (3) to 10 apology strategies out of the total 17 apology strategies. Second, the 50 Malaysian public apology texts focused dominantly on eight (8) apology strategies that reflected features of: a) AS 11 (Offer Repair to Rectify the Wrongdoing), b) AS 10 (Downgrade the Harm), c) AS 4 (Justify the Wrongdoing / Action), d) AS 9 (Acknowledge the Harm Resulting from the Wrongdoing), e) AS 5 (Explain the Wrongdoing/ Action), f) AS 6 (Admit One’s Responsibility for the Wrongdoing/ Action), g) AS 2 (Show the Intention to Apologize) and h) AS 3 (Intensify the Intention to Apologize). Third, both positive and negative politeness strategies were found across the Malaysian public apology texts. The 16 apology strategies found across the 50 public apology texts reflected the use of 11 positive politeness strategies and six (6) negative politeness strategies. Fourth, across the 16 apology strategies, the two (2) most dominant positive politeness strategies present were: a) PPS 1 (Notice, attend to Receiver (his interests, wants, needs, goods) and b) PPS 10 (Offer, promise), and the two (2) most dominant negative politeness strategies used were: a) NPS 6 (Apologize) and b) NPS 4 (Minimize the Imposition). There were three (3) conclusions. First, the content of the Malaysian public apology texts did reflect the use of politeness in terms of the use of some apology strategies and positive and negative politeness strategies. Second, the Malaysian public apology texts included dominant apology strategies relevant to apologies. Third, the Malaysian public apology texts reflected the use of both positive and negative politeness strategies suggesting that focus was given to maintaining positive public self-image and relationships and giving respect to the apologizees. Four (4) recommendations were proposed. First, there should be formal instruction on public apologies focusing on internationally acceptable standards and criteria of politeness in terms of use of apology strategies and pragmatic politeness strategies at secondary, tertiary and professional levels of education. Second, the designers of education syllabus and book writers should incorporate apology strategies and pragmatic politeness strategies in their respective syllabus and academic books for effective writing of public apologies. Third, teachers, academicians, educators and journalists should optimize the data of this study for further understanding and improvement of current practices of public apologies in the Malaysian context. Fourth, this study should be used as guidelines for further research on public apologies in important contexts of business, medicine, legislation, politics, and religion.